The Axisymmetric Slow Viscous Flow about a Shear Stress Free Sphere (Global Journal of Science Frontier Research, 2015)
Harper's sphere theorem for the axisymmetric slow viscous flow exterior to a shear stress-free sphere is established in an alternative way and then given an extension of the theorem for the flow interior to the same sphere.
Keywords: harper's theorem; viscous flow; shear stress; circle theorem